Estimated burden of fungal infections in Germany. (9th October 2015) - Ruhnke, Markus; Groll, Andreas H.; Mayser, Peter; Ullmann, Andrew J.; Mendling, Werner; Hof, Herbert; Denning, David W.; ,
Summary: In the late 1980's, the incidence of invasive fungal diseases (IFDs) in Germany was estimated with 36.000 IFDs per year. The current number of fungal infections (FI) occurring each year in Germany is still not known. In the actual analysis, data on incidence of fungal infections in various patients groups at risk for FI were calculated and mostly estimated from various (mostly national) resources. According to the very heterogenous data resources robust data or statistics could not be obtained but preliminary estimations could be made and compared with data from other areas in the world using a deterministic model that has consistently been applied in many countries by the LIFE program (www.LIFE-worldwide.org ). In 2012, of the 80.52 million population (adults 64.47 million; 41.14 million female, 39.38 million male), 20% are children (0–14 years) and 16% of population are ≥65 years old. Using local data and literature estimates of the incidence or prevalence of fungal infections, about 9.6 million (12%) people in Germany suffer from a fungal infection each year. These figures are dominated (95%) by fungal skin disease and recurrent vulvo‐vaginal candidosis. In general, considerable uncertainty surrounds the total numbers because IFDs do not belong to the list of reportable infectious diseases in Germany and most patients were not hospitalised because of the IFD but a distinct underlying disease.